Wayfinding techniques for multiscale virtual environments - Silva, Felipe Bacim de Araújo e (2009)
Wayfinding in multiscale virtual environments can be rather complex, as users can and sometimes have to change their scale to access the entire environment. Hence, this work focuses on the understanding and classification of information needed for travel, as well as on the design of navigation techniques that provide this information. To this end, we first identified two kinds of information necessary for traveling effectively in this kind of environment: hierarchical information, based on the hierarchical structure formed by the levels of scale; and spatial information, related to orientation, distance between objects in different levels of scale and spatial localization. Based on this, we designed and implemented one technique for each kind of information. The developed techniques were evaluated and compared to a baseline set of travel and wayfinding aid techniques for traveling through multiple scales. Results show that the developed techniques perform better and provide a better solution for both travel and wayfinding aid.